Study Muscle Movements with Arduino - Abdullah, Maryam Khalid; Hameed, Saba Thamer; Fadhil, Rehab Saad (Journal of Science in Medicine and Life, 2024)
Electromyography (EMG) devices are well-suited for measuring the behaviour of muscles during an exercise or a task, and are widely used in many different research areas. Their disadvantage is that commercial systems are expensive. We designed a low-cost EMG system with enough accuracy to be used in a wide range of possible ways. The present research focuses on the validation of the low-cost system we designed, which is compared with a commercially available, accurate device. The evaluation was done by means of a set of experiments, in which volunteers performed isometric and dynamic exercises while EMG signals from the hand were registered by both the proposed low-cost system and a commercial system simultaneously. Analysis and assessment of two indicators to estimate the similarity between both signals were developed. These indicated a very good result.